2010
DOI: 10.1210/me.2009-0498
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Represses Colon Cancer Cell Proliferation via AdipoR1- and -R2-Mediated AMPK Activation

Abstract: In obesity, dysregulation of adipocytokines is involved in several pathological conditions including diabetes and certain cancers. As a member of the adipocytokines, adiponectin plays crucial roles in whole-body energy homeostasis. Recently, it has been reported that the level of plasma adiponectin is reduced in several types of cancer patients. However, it is largely unknown whether and how adiponectin affects colon cancer cell growth. Here, we show that adiponectin suppresses the proliferation of colon cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(119 citation statements)
references
References 58 publications
5
111
0
3
Order By: Relevance
“…Also, it has been shown that adiponectin mediates expression of cell cycle regulatory proteins and activates AMPK signalling in colon cancer cell lines 41. Similar to these reports, we observed that the suppressive effect of adiponectin on colon cancer cell proliferation was mediated by activation of AMPK and/or decreasing phosphorylation of S6.…”
Section: Discussionsupporting
confidence: 90%
“…Also, it has been shown that adiponectin mediates expression of cell cycle regulatory proteins and activates AMPK signalling in colon cancer cell lines 41. Similar to these reports, we observed that the suppressive effect of adiponectin on colon cancer cell proliferation was mediated by activation of AMPK and/or decreasing phosphorylation of S6.…”
Section: Discussionsupporting
confidence: 90%
“…Adiponectin plays an important role in energy metabolism and has insulin-sensitizing and anti-inflammatory properties [53,8]. In addition, anti-neoplastic properties such as inhibition of proliferation and promotion of apoptosis have been observed to be upregulated by adiponectin in cancer cells [54]. High adiponectin concentrations have been suggested to play a protective role in the development of cancer either directly through inhibition of cell growth and induction of apoptosis or indirectly through improved insulin sensitivity and reduced inflammation [54].…”
Section: Adiponectinmentioning
confidence: 99%
“…In addition, anti-neoplastic properties such as inhibition of proliferation and promotion of apoptosis have been observed to be upregulated by adiponectin in cancer cells [54]. High adiponectin concentrations have been suggested to play a protective role in the development of cancer either directly through inhibition of cell growth and induction of apoptosis or indirectly through improved insulin sensitivity and reduced inflammation [54]. Epidemiological evidence for an association between pre-diagnostic adiponectin concentrations and obesity-associated cancer has emerged from several investigations.…”
Section: Adiponectinmentioning
confidence: 99%
“…Adiponectin negatively influences growth of most obesity-related cancer types, such as prostate [157] and colon [158] cancers. A study on breast cancer also proved a negative effect of adiponectin on migration [159].…”
Section: Introductionmentioning
confidence: 99%